Impact of GlobalGAP certification on EU banana imports: A gravity modeling approach - Amjad Masood; Bernhard Brümmer (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2014)
Adopting a gravity framework and using data from 2010 to 2012 for 74 countries, we investigate whether the intensity of GlobalGAP standard adoption has a positive impact on EU banana import values. Intensity is measured by using number of GlobalGAP certified producers and hectares harvested under GlobalGAP certification. Using random and fixed effect estimation we find that intensity of certification, in terms of producers and hectares are associated with higher banana imports. However the estimated elasticities of imports in all models are less than 1 indication an inelastic response of imports to GlobalGAP certification intensity. This also indicates that the small farmers in developing countries who find it difficult to comply with the GlobalGAP standard requirements are driven out of the international banana market. For the gravity variables distance is found to have negative impact, but banana production in the exporting countries and presence of common language and RTA between the trading countries improves trade.
Keywords: 330; Banana imports of EU; Private food standard; GlobalGAP; Gravity model